Neu Differentiation Factor Stimulates Phosphorylation and Activation of the Sp1 Transcription Factor - Alroy, Iris (American Society for Microbiology, 1999)
Neu differentiation factors (NDFs), or neuregulins, are epidermal growth factor-like growth factors which bind to two tyrosine kinase receptors, ErbB-3 and ErbB-4. The transcription of several genes is regulated by neuregulins, including genes encoding specific subunits of the acetylcholine receptor at the neuromuscular junction. Here, we have examined the promoter of the acetylcholine receptor ɛ subunit and delineated a minimal CA-rich sequence which mediates transcriptional activation by NDF (NDF-response element [NRE]). Using gel mobility shift analysis with an NRE oligonucleotide, we detected two complexes that are induced by treatment with neuregulin and other growth factors and identified Sp1, a constitutively expressed zinc finger phosphoprotein, as a component of one of these complexes. Phosphatase treatment, two-dimensional gel electrophoresis, and an in-gel kinase assay indicated that Sp1 is phosphorylated by a 60-kDa kinase in response to NDF-induced signals. Moreover, Sp1 seems to act downstream of all members of the ErbB family and thus may funnel the signaling of the ErbB network into the nucleus.